ANALYSIS OF POLYSOMNOGRAPHY VARIABLES ON MALE SPORTS PERSONS IN RESPONSE TO YOGA NIDRA - Deol, Nishan Singh; Singh, Amrinder; Rani, Savita (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The purpose of this study was to compare polysomnography variables on male sports persons. The subjects for the present study were consisting of Ten (N=10), Male Sports persons i.e., Kabbadi and Volleyball Players of Punjabi university, Patiala, Punjab. After preparing the list of subject’s age ranged from 21-25 years, the investigator checked the health record of these subjects maintained by the health department of the university to ensure that the subjects were medically fit to undergo the different types of tests. The selection of the appropriate polysomnography variables between male sports persons the researcher had chosen the factors for the investigation in Response to Yoga Nidra i.e., time in bed, sleeps time, sleep efficiency, sleep onset latency, rapid eye movement.The Statistical Package for the Social Sciences (SPSS) version 21 was used for all analyses. The differences in the mean of each group i.e. Sports persons (Kabbadi and Volleyball Players) for selected polysomnography variable were tested for the significance of difference by applying paired samples „t‟ test. For testing the hypotheses, the level of significance was set at 0.05 percent (p<0.5).To conclude, it is significant to mention in relation to Time in Bed that results of Analysis of Variance (ANOVA) among Male Sports Persons i.e., Kabbadi and Volleyball Players (N=10) were found statistically insignificant (P> .05). Furthermore, in relation to Total Sleep Time, Sleep Efficiency, Sleep Onset Latency, Rapid Eye Movement that result of Analysis of Variance (ANOVA) among Male Sports Persons i.e., Kabbadi and Volleyball Players (N=10) was found statistically significant (P< .05).